Microstructure and mechanical properties of Selective Laser Melted Ti-6.5Al-2Zr-1Mo-1V alloy. (1st March 2023) - Nie, Xuan; Song, Xiaoyun
Abstract: Selective laser melting (SLM) offers a new solution to the production of complex-shaped Ti-6.5Al-2Zr-1Mo-1V(TA15) alloy components with the advantage of low weight and high performance in the aerospace industry. In this paper, Ti-6.5Al-2Zr-1Mo-1V samples with relative density > 99.5% were fabricated by SLM. The microstructure of SLMed samples is composed of numerous prior-β grains and interior acicular α′ martensite, exhibiting extremely high strength but poor plasticity. After heat treatment, the ultimate tensile strength(UTS) and yield strength(YS) are reduced by various degrees, while the plasticity is obviously improved owing to the decomposition and transformation of α′ martensite.